Achieving customer loyalty during post-pandemic: an asymmetric approach - Khawaja Fawad Latif; Shahid Bashir (Future Business Journal)
Abstract The study aims to investigate causal recipes to improve restaurant customers’ loyalty (LOY) during COVID-19 post-pandemic. The study utilizes Fuzzy-set Qualitative Comparative Analysis (fsQCA) within the framework of complexity theory to examine the intricate relationship between antecedent conditions, including Socially Responsible COVID-19 practices (CSR), Service Quality (SR), Customer Experience (EXP), Customer Satisfaction (SAT), Trust (TR), and Customer Commitment (COMM). The study used a quantitative survey approach, using a Likert scale to achieve the study aim. The survey has been strategically developed to gather intricate replies, taking influence from well-established scales within the area. The research purposefully recruited customers from the restaurant industry in Pakistan. A total of 450 full and valid replies were obtained via the use of Google Forms and paper questionnaires. The fsQCA approach is used to examine the data and ascertain configurations or combinations of antecedent situations that contribute to enhanced levels of loyalty. The results indicate that LOY is a multifaceted phenomenon in the post-pandemic phase of COVID-19 and is not only influenced by individual antecedent situations. This study identifies many routes that lead to increased levels of loyalty, highlighting the need to adopt a comprehensive and integrated strategy. The research emphasizes the diverse impacts of important factors, including CSR, SR, EXP, SAT, TR, and COMM, on loyalty. The novelty of this study is in its utilization of fsQCA and complexity theory to investigate LOY inside the restaurant sector among the distinctive circumstances of the post-pandemic period of COVID-19. This paper presents a critique of conventional symmetrical methods and proposes a comprehensive viewpoint on LOY, highlighting the need for sophisticated and integrated theoretical frameworks. Through the exploration of several routes to increased levels of LOY and the identification of the intricate influences of numerous preceding factors, this study enhances both theoretical and practical comprehension. The study places significant importance on an innovative research methodology and its potential impact on restaurant management, making it a noteworthy contribution to the current body of literature.